2021
DOI: 10.1002/brb3.2318
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Psychological effects of the COVID‐19 pandemic: Perceived stress, anxiety, work–family imbalance, and coping strategies among healthcare professionals in Khartoum state hospitals, Sudan, 2021

Abstract: Background:The 2019 novel coronavirus (COVID-19) is highly contagious and can spread a pandemic, so it is related to serious health issues and major public concerns, and is considered by the medical community to be the greatest concern because it is the greatest risk of infection.Objective: To identify and assess the psychological effects of the COVID-19 pandemic on healthcare professionals in Khartoum state hospitals 2021.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
5
19
0
4
Order By: Relevance
“…43 Another study concluded that more than half of HCPs working in Khartoum state hospitals showed high levels of stress. 44 Due to the fragile health system in Sudan, political instability and economic meltdown; medical personnel have to work under high pressure in a very limited infrastructure, and as a sequel working under stress and pressure can be from the leading factors that makes health professionals more prone to burnout. 44,45 In the current study, the majority of HCPs of both countries had high levels of disengagement (75.4%) and emotional exhaustion (98.6%) which is higher than the ndings among the Italian nurses which showed high levels of exhaustion( 76%) and disengagement (52%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Another study concluded that more than half of HCPs working in Khartoum state hospitals showed high levels of stress. 44 Due to the fragile health system in Sudan, political instability and economic meltdown; medical personnel have to work under high pressure in a very limited infrastructure, and as a sequel working under stress and pressure can be from the leading factors that makes health professionals more prone to burnout. 44,45 In the current study, the majority of HCPs of both countries had high levels of disengagement (75.4%) and emotional exhaustion (98.6%) which is higher than the ndings among the Italian nurses which showed high levels of exhaustion( 76%) and disengagement (52%).…”
Section: Discussionmentioning
confidence: 99%
“…44 Due to the fragile health system in Sudan, political instability and economic meltdown; medical personnel have to work under high pressure in a very limited infrastructure, and as a sequel working under stress and pressure can be from the leading factors that makes health professionals more prone to burnout. 44,45 In the current study, the majority of HCPs of both countries had high levels of disengagement (75.4%) and emotional exhaustion (98.6%) which is higher than the ndings among the Italian nurses which showed high levels of exhaustion( 76%) and disengagement (52%). 31 Our results were close to results of healthcare workers in Singapore which revealed 79.7% disengagement and 75.3% exhaustion with mean OLBI scores 2.38 and 2.50 for disengagement and exhaustion respectively 4 close to the mean scores of the current study which were 2.56 and 2.73 for disengagement and exhaustion respectively .…”
Section: Discussionmentioning
confidence: 99%
“…[ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] The prevalence of depressive symptoms ranged between 32.1%–94.0%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] Most of these studies used the Generalized Anxiety Disorder 7 (GAD-7) [ 11 , 12 , 15 , 16 , 23 , 24 , [26] , [27] , [28] ] and Patient Health Questionnaire 9 (PHQ-9) [ 12 , 15 , 23 , 24 , 26 , 28 ] to determine anxiety and depression. Other data collection tools included the 10-item Cohen Perceived Stress Scale [ 10 , 26 , 27 , 29 ], 14-item Shirom-Melamed Burnout measure [ 10 ], 7-item Insomnia Severity Index [ 12 , 26 , 28 , 30 ], 22-item Impact of Event Scale-Revised [ 12 , 28 ], 16-item Stanford Professional Fulfilment Index [ 12 , 28 ], Hospital Anxiety Depression Score [ 13 ], Coronavirus Anxiety Scale [ 17 ] and Primary Care PTSD Screen.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of a recent multi-country study on the mental health impacts among HCPs in the Eastern Mediterranean Region (EMR), HCPs in Egypt, Iraq, and Sudan demonstrated the highest depression, anxiety, and stress scores compared to those in other countries in EMR [46]. Furthermore, in a recent study that assessed the perceived stress among health professionals in Sudan during the COVID-19 pandemic, more than half of HCPs demonstrated high-stress levels, and most of them had a poor work-family balance [47]. The prevalence rate of BOS in this study was similar to a study conducted among resident physicians in Greece, in which 14.4% of residents met the criteria for BOS [28].…”
Section: Discussionmentioning
confidence: 99%